Rozprawa o wolnomyślicielstwie (1713) Anthony’ego Collinsa (Przegląd Religioznawczy – The Religious Studies Review, 2022)
In this paper, I classify and briefly discuss the variety of arguments for freedom of thought summoned by the English free-thinker Anthony Collins (1676–1729) in his formerly controversial and influential book entitled A Discourse of Free-Thinking, Ocasion’d by the Rise and Growth of a Sect call’d Free-Thinkers (1713). I argue that some of them are indeed reasonable or partly reasonable.